2019
DOI: 10.1021/acs.energyfuels.8b04417
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Modeling Study on Autoignition of a Biodiesel/n-Heptane Mixture and Related Surrogate in a Heated Rapid Compression Machine

Abstract: In this paper, ignition delay time of two kinds of biodiesel, soybean oil methyl ester (SME) and waste cooking oil methyl ester (WCOME) blended with n-heptane, were measured in a heated rapid compression machine (RCM). To meet the requirement of measuring high boiling fuels like biodiesel, several modifications were applied in RCM platform, which embodied in global preheating, reactant preparation, and gas dilution. Along with these methodologies, ignition delay times of SME30 and WCOME30 (30% biodiesel and 70… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…A number of studies on biodiesels and excellent reviews on this topic (both fundamental studies and biodiesel utilization) can be found in the literature. ,, The common findings noted in the current literature include the following: (i) biodiesels can be made from different feedstock and could be a potential candidate to partly replace fossil diesel used in compression ignition engines , and these biofuels could be blended with fossil diesel with or without additives, (ii) biodiesels have a higher cetane number but a lower calorific value and higher viscosity compared to fossil diesel, , and (iii) fueling engines with biodiesels can help to decrease specific particulate matter in mass basic, while the effect of biodiesels on NO x formation and particle number and size distribution is not fully understood. , Further investigations of physical and chemical properties of biodiesels made from different feedstock are essential to have a comprehensive understanding of the engine performance when operating with biodiesels. The impact of FAME profiles, especially oxygen content, on the properties of biodiesels made from different feedstock, and the influence of fuel properties on fuel atomization and evaporation, according to the authors’ knowledge, is not quite clear in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies on biodiesels and excellent reviews on this topic (both fundamental studies and biodiesel utilization) can be found in the literature. ,, The common findings noted in the current literature include the following: (i) biodiesels can be made from different feedstock and could be a potential candidate to partly replace fossil diesel used in compression ignition engines , and these biofuels could be blended with fossil diesel with or without additives, (ii) biodiesels have a higher cetane number but a lower calorific value and higher viscosity compared to fossil diesel, , and (iii) fueling engines with biodiesels can help to decrease specific particulate matter in mass basic, while the effect of biodiesels on NO x formation and particle number and size distribution is not fully understood. , Further investigations of physical and chemical properties of biodiesels made from different feedstock are essential to have a comprehensive understanding of the engine performance when operating with biodiesels. The impact of FAME profiles, especially oxygen content, on the properties of biodiesels made from different feedstock, and the influence of fuel properties on fuel atomization and evaporation, according to the authors’ knowledge, is not quite clear in the literature.…”
Section: Introductionmentioning
confidence: 99%